Light sheet fluorescence microscopy as a new method for unbiased three-dimensional analysis of vascular injury. Issue 2 (13th February 2020) - Buglak, Nicholas E; Lucitti, Jennifer; Ariel, Pablo; Maiocchi, Sophie; Miller, Francis J; Bahnson, Edward S M
Abstract: Aims: Assessment of preclinical models of vascular disease is paramount in the successful translation of novel treatments. The results of these models have traditionally relied on two-dimensional (2D) histological methodologies. Light sheet fluorescence microscopy (LSFM) is an imaging platform that allows for three-dimensional (3D) visualization of whole organs and tissues. In this study, we describe an improved methodological approach utilizing LSFM for imaging of preclinical vascular injury models while minimizing analysis bias. Methods and results: The rat carotid artery segmental pressure-controlled balloon injury and mouse carotid artery ligation injury were performed. Arteries were harvested and processed for LSFM imaging and 3D analysis, as well as for 2D area histological analysis. Artery processing for LSFM imaging did not induce vessel shrinkage or expansion and was reversible by rehydrating the artery, allowing for subsequent sectioning and histological staining a posteriori . By generating a volumetric visualization along the length of the arteries, LSFM imaging provided different analysis modalities including volumetric, area, and radial parameters. Thus, LSFM-imaged arteries provided more precise measurements compared to classic histological analysis. Furthermore, LSFM provided additional information as compared to 2D analysis in demonstrating remodelling of the arterial media in regions of hyperplasia and periadventitial neovascularization around the ligated mouse artery. Conclusion: LSFM provides a novel and robust 3D imaging platform for visualizing and quantifying arterial injury in preclinical models. When compared with classic histology, LSFM outperformed traditional methods in precision and quantitative capabilities. LSFM allows for more comprehensive quantitation as compared to traditional histological methodologies, while minimizing user bias associated with area analysis of alternating, 2D histological artery cross-sections.